Latihan Nafas Modifikasi Meniup Balon Terhadap Pengembangan Paru pada Pasien Hematothoraks dan Pneumothoraks - Tintin Sukartini; Sriyono Sriyono; Nursalam Nursalam; Ninuk Dian Kurniawati; Adi Sukrisno (Universitas Airlangga, 2007)
Collaps is a condition of the absence of air in alveoli. Lung collaps result from the presence of air or blood in the cavity. Modified ballon blowing respiratory exercise is intended to improve lung ventilation,increase vital capacity and preven atelectasis. The objective of this study was to analyze the effect of modified ballon blowing respiratory on lung compliance in pneumothorax and haemathorax. A quasy experimental design was used in this study with 10 respondens who met the inclusion criteria. The independent variabel was modified ballon blowing respiration exercise and the dependent variable was lung compliance by observing thorax foto, repiratory rate and vital capacity. Data were analyzed by using t test, Mc.Nemar and chi square test. The results showed that modified ballon blowing respiratory execise is effective to assit lung compliance with significant level on vital capacity (p=0.018).